Thromboelastography (TEG®) demonstrates that tinzaparin 4500 international units has no detectable anticoagulant activity after caesarean section. (February 2017) - Griffiths, S.; Woo, C.; Mansoubi, V.; Riccoboni, A.; Sabharwal, A.; Napier, S.; Columb, M.; Laffan, M.; Stocks, G.
Highlights: Tinzaparin 4500 i.u. is not detectable by TEG® up to 10 h post administration. Tinzaparin 4500 i.u. has no effect on anti-Xa assay up to 10 h post administration. Findings support the guidelines on thromboprophylaxis timing & epidural insertion. Abstract: Background: Low molecular weight heparin is routinely used for thromboprophylaxis in pregnancy and the puerperium. Consensus guidelines recommend waiting 10–12 h after administration of a thromboprophylactic dose of low molecular weight heparin before performing a neuraxial block or removing an epidural catheter. Thromboelastography (TEG®) has been reported to be sensitive to the effects of enoxaparin 4 h after administration. The purpose of this study was to use TEG to examine coagulation changes in the first 10 h after a thromboprophylactic dose of tinzaparin in an attempt to ratify the current consensus guidelines about timing of neuraxial blockade and epidural catheter removal. Methods: Twenty-four women who had undergone caesarean delivery and were classified as low or intermediate risk of thrombosis were recruited. Blood samples were taken before subcutaneous administration of tinzaparin 4500 IU, and at 4, 8 and 10 h post-dose. Standard TEG analyses were performed using plain and heparinase cuvettes and samples were also sent for laboratory anti-Xa assay. Thromboelastograph profiles were analysed for a low molecular weight heparin effect. Results: Analysis revealed no significant differences in R time, K time, alpha angle or maximum amplitude between plain and heparinase samples at any time point. Apart from a small statistically significant ( P =0.033) decrease in maximum amplitude of 2.8% (95% CI 0.3 to 5.4%) at 4 h, there were no significant changes in coagulation for any TEG parameter. Anti-Xa levels were virtually undetectable in all patients over the 10 h period (median 0.00 U/mL; range 0.00–0.13 U/mL). Conclusion: A thromboprophylactic dose of tinzaparin 4500 IU had little detectable effect on coagulation as assessed by TEG and anti-Xa assay. These findings support consensus guidelines which state that it is acceptable to perform neuraxial blockade or remove an epidural catheter 10–12 h after a thromboprophylactic dose of tinzaparin. Rather than suggesting a lack of anticoagulant activity, the findings indicate that TEG may not have the sensitivity to detect a tinzaparin effect when this dose is used in this patient group.